ASESMEN RISIKO BENCANA TERHADAP TEBING SUNGAI WINONGO: (Studi Kasus : Sungai Winongo Bagian Hulu) - Puji Harsanto; Nazrey Rahario Nugroho; Restu Faizah; Nursetiawan Nursetiawan (Racic : Rab Construction Research, 2024)
The Winongo River originates in the Opak River and has many potential hazards such as flooding, cold lava floods and riverbank landslides, so a disaster risk analysis is necessary. The research area is located in the headwaters of the river which passes through the villages of Sendangadi, Sinduadi, Trihango, Bener, Tegalrejo and Pakuncen. The method used is semi-quantitative and qualitative, using tabular data and numerical assessment of land use, population and river hydrology. With the AHP (Analytical Hierarchy Process) method which determines the best choice from several supporting data. The method of determining disaster risk by weighting follows the Regulation of the Director General of BNPB Year 2012. A disaster risk assessment using the AHP method obtained a score of 1.1 in Sendangadi Village, 1.6 in Sinduadi Village. Trihanggo has a value of 1.1, Bener has a value of 1.3, Tegalrejo has a value of 1.4, and Pakuncen has a value of 1.5. Sendangadi and Trihango villages have the lowest risk level with the same value of 1.1. From the results of the disaster risk analysis it has been found that in all sub-districts that are flowed by the upstream Winongo River, they have a low level of risk.